- Maize Nugget Making in Nagari Ladang Panjang, Pasaman Regency, West Sumatra: Pembuatan Nugget Jagung di Nagari Ladang Panjang, Kabupaten Pasaman, Sumatera Barat - I Ketut Budaraga; Eddwina Aidila Fitria (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract Nugget is a processed meat products which mixed or without other ingredients and permitted food additives. In its manufacture, the nugget is formed and then steamed and fried before being consumed. One of the most widely grown horticultural crops in the Nagari Ladang Panjang area is corn. Corn can be used as nuggets which are rich in fiber and added tofu as its protein. The purpose of this activity is to provide knowledge to the community about making sweet corn-based nuggets. The results of the implementation of this service were successful in processing and the community was very enthusiastic. This corn nuggets product can be used as an alternative in consuming vegetable protein and fiber. If these corn nuggets are developed properly, they can become one of the superior products in the form of frozen food from Nagari Ladang Panjang. Keywords: nuggets, sweet corn, tofu, frozen food